KINERJA PERTUMBUHAN DAN KELANGSUNGAN HIDUP UDANG VANAME Litopenaeus vannamei DENGAN JENIS DAN FREKUENSI PAKAN BERBEDA DI KERAMBA JARING APUNG - Irawati, Irawati; Arif, Deslilna; Damaris, Payung (Universitas Teuku Umar, 2020)
This study about “Growth & survival rate performance of vaname shrimp Litopenaeus Vannamei by different of type and frequency feed in floating cage net, fisheries high school (SUPM) Ambon. Implementation of the study lasted for 6 (six) months from January to June 2016. The study design was used completely randomized design (CRD) factorial using two factors as a treatment that: (1) the feed type of sardine and squid & sardine’s combination, (2) feeding frequency of 2 times and 3 times, to see whether there are significant differences between the treatment of the growth and survival of shrimp vaname as samples. From the research data were analyzed using ANOVA (analysis of variance) showed that the type of feed and feeding frequency are significant effect on the rate of growth of shrimp vaname. For optimal growth rate (absolute weight) in the treatment p2f2 with a value of 20.62 g. As for the survival of shrimp vanname no significant effect.